The Computer Crimes of Vasiliy Gorshkov and Alexey Ivanov - Buresh, Donald L. (Journal of Advanced Forensic Sciences, 2022)
The purpose of this essay was to document the cybercrimes of Vasiliy Gorshkov and Alexey Ivanov, starting from their humble beginnings in Chelyabinsk, Russia to their convictions for conspiracy, violations of the Computer Fraud and Abuse Act, and other federal crimes. The paper outlines the history of these two individuals, describing the circumstances under which they were arrested and prosecuted. The essay concludes by observing that the mainstream media characterized Gorshkov and Ivanov as villainous Russian hackers, whereas in reality, they were would-be Russian entrepreneurs attempting to earn their fortune by illicit means.
Keywords: Alexey Ivanov; American exceptionalism; Computer Fraud and Abuse Act; Extra-Territorial Computer Searches; Special Prosecutor Robert Mueller; Vasiliy Gorshkov